Decoupling Electron‐ and Phase‐Transfer Processes to Enhance Electrochemical Nitrate‐to‐Ammonia Conversion by Blending Hydrophobic PTFE Nanoparticles within the Electrocatalyst Layer. Issue 9 (15th January 2023) - Gao, Jianan; Ma, Qingquan; Young, Joshua; Crittenden, John C.; Zhang, Wen
Abstract: Electrochemical upcycling of nitrate into ammonia at ambient conditions offers a sustainable synthesis pathway that can complement the current industrial NH3 production from the Haber–Bosch process. One of the key rate‐limiting steps is the effective desorption of gaseous or interfacial bubble products, mainly NH3 with some minor side products of nitrogen and hydrogen, from the electrode surfaces to sustain available sites for the NO3 − reduction reaction. To facilitate the gaseous product desorption from the catalytic sites, hydrophobic polytetrafluoroethylene (PTFE) nanoparticles are blended within a CuO catalyst layer, which is shown to eliminate the undesirable accumulation and blockage of electrode surfaces and largely decouples the electron‐ and phase‐transfer processes. The NH3 partial current density normalized by the electrochemically active surface area (ECSA) increases by nearly a factor of 17.8 from 11.4 ± 0.1 to 203.3 ± 1.8 mA cm −2 ECSA . The DFT and ab‐initio molecular dynamics simulations suggest that the hydrophobic PTFE nanoparticles may serve as segregated islands to enhance the spillover and transport the gaseous products from electrocatalysts to the PTFE. Thus, a higher ammonia transfer is achieved for the mixed PTFE/CuO electrocatalyst. This new and simple strategy is expected to act as inspiration for future electrochemical gas‐evolving electrode design. Abstract : Blending hydrophobic polytetrafluoroethylene nanoparticles into the model CuO catalyst layer is demonstrated for the first time to enhance the spillover/transport of gaseous products from the electrocatalyst surface and enhance the nitrate‐to‐ammonia yield in electrochemical membrane stripping.